National security and counterintelligence in the era of cyber espionage - Silva, Eugenie de, 1998 (Hershey : Information Science Reference, 2016)
'This book highlights technological advancements in intelligence systems and law enforcement in relation to cybercrime and reconnaissance issues, focusing on current and emergent threats to national security, as well as the technological advancements being adopted within the intelligence field'--
Includes bibliographical references and index.
Keywords: Computer crimes; Intelligence service; Intelligence service -- Computer networks; National security -- Law and legislation